Penerapan Pembelajaran Bahasa Indonesia Berbasis Kurikulum Merdeka di MTs - Septi Amanda; Hindun Hindun (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The purpose of this study is to obtain information related to the Application of Independent Curriculum-Based Indonesian Learning at MTs Al-hidayah Cinangka Sawangan Depok. Researchers use qualitative descriptive methods. The descriptive method in this study is used to describe how the Application of Independent Curriculum-Based Indonesian Learning. The data collection technique carried out by researchers in this study is interviews, First, interviews. Researchers use interviews that are semi-structured. The semi-structured interview itself aims to explore all forms of problems more openly, where all parties who are the object of the interview will be asked for their opinions and ideas. To get data, researchers focus on listening and recording everything released by the object being interviewed. Then the second is the study of documentation. The documentation in this study aims to record all data from the results of interviews that have been conducted with Indonesian subject teachers. The results showed that the Application of Independent Curriculum-Based Indonesian Learning has been implemented and is ongoing. However, in its application there are obstacles and still trying to re-streamline the application of this independent curriculum with the previous curriculum.